Teacher Strategies in Overcoming Reading Difficulties in Class II MI Intisyarul Ulum Students - Islam, Muhammad Hifdil; Badruttamam, Choerul Anwar; Azizah, Zakiyah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study aims to investigate the strategies used by grade 2 teachers in overcoming students' reading difficulties. The method used in this research is descriptive qualitative with data collection techniques through interviews, observation and documentation. The data analysis technique uses technical triangulation, namely by applying different techniques to the same source in checking the data. Through research activities at MI Intisyarul Ulum Sumber Taman, specifically at grade II level, it was found that there were still many students who had not mastered reading skills and some even could not read. This happens because there are several factors that influence students' lack of reading skills at school. For this reason, teachers must have a strategy so that students no longer find it difficult to read. The results of the research show that the strategies used by grade 2 teachers in overcoming students' reading difficulties are: (1) Utilizing reading corners, (2) Getting into the habit of always reading together during the learning process, both reading aloud and reading silently, (3) Directing. and motivate students to continue learning to read